An experimental investigation of sessile droplets evaporation on hydrophilic and hydrophobic heating surface with constant heat flux. (November 2017) - Gao, Ming; Kong, Peng; Zhang, Li-Xin; Liu, Jing-Nan
Abstract: Droplet evaporation widely exists in the daily life and industrial production. In most of previous experimental studies, the evaporation of sessile droplets was conducted under a constant substrate temperature condition. However, drops often evaporating on a heating surface under a constant heat flux condition in many practical applications. In this paper, we have carried out an experiment on sessile 3 μl DI water droplets evaporated on hydrophilic and hydrophobic heating surfaces under constant heat flux in the range from 1153 W/m 2 to 6919 W/m 2 . A high-speed camera was used to record the changing shapes of two sessile droplets on a hydrophilic and a hydrophobic heating surface placed side by side. The droplet height, dynamic contact angle, droplet contact diameter, evaporation mode and evaporation rate are presented.